Carbon stocks and changes of dead organic matter in China's forests - Jianxiao Zhu (Nature Portfolio, 2017)
Reliable estimates of the total forest carbon (C) pool are lacking due to insufficient information on dead organic matter (DOM). Here, the authors estimate that the current DOM C stock in China is 925 ± 54 Tg and that it grew by 6.7 ± 2.2 Tg C/yr over the past two decades primarily due to increasing forest area